THE RELATIONSHIP BETWEEN STUDENTS' ABILITY TO PRONOUNCE THE LETTERS OF THE ALPHABET AND THE EDUCATIONAL ACHIEVEMENT OF THE DICTATION COURSE IN THE INTERMEDIATE STAGE AT AL-KAUTSAR BOARDING SCHOOL - Arpin Aminuddin Hrp; Slamet Riyadi; Arbonas Lubis (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2022)
The relationship between students' ability to pronounce the letters of the alphabet and the educational achievement of the dictation course in the intermediate stage at Al-Kautsar boarding schoolThis study aims to determine the ability of students in pronouncing hijaiyyah letters and the correlation between  students’ ability in pronouncing hijaiyyah letters with the score of imla’ subject. The method used in this study is quantitative in the form of correlation, to analyze the data the writer uses statistics, because this is the appropriate method to obtain the data and results of this study. The results show that the student’s ability to pronounce hijaiyyah letters is 76,00 with a very good predicate, while the correlation between students’ ability in pronouncing hijaiyyah letters and the score of imla’ subject is r-count 0,728 and r-table is 0,202 then the Ha hypothesis is accepted and the Ho hypothesis is rejected because r-count is greater than r-table. The canculesion is that there is a positive correlation between students’ ability to pronounce hijaiyyah letters and the score of imla’ sabject. العلاقة بين قدرة الطلاب على نطق الحروف الهجائية والتحصيل التعليمي لمادة الإملاء في المرحلة المتوسطة بمعهد الكوثرهذا البحث يهدف إلى معرفة قدرة الطلاب على نطق الحروف الهجائية في المرحلة المتوسطة الصف الثاني بمعهد الكوثر، ووجود العلاقة بين قدرة الطلاب على نطق الحروف الهجائية والتحصيل التعليمي لمادة الإملاء. والمنهج المستخدم هو المدخل الكمي الميداني بالنوع العلاقي والطريقة المستخدمة هي طريقة إحصائية، لأن رأى الباحث هي الطريقة المناسبة لحصول على جمع البيانات أو نتائج البحث. والنتيجة أن قدرة الطلاب على نطق الحروف الهجائية 76،00 بدرجة جيد جدا لأن النتيجة وقعت بين 66-73، والعلاقة بين قدرة الطلاب على نطق الحروف الهجائية والتحصيل التعليمي لمادة الإملاء rhitung في هذا البحث هي 0،728 وأما rtabel هي 0،202 فالفرضية التبادلية مقبولة والفرضية العدمية مردودة حيث rhitung أكبر من rtabel. والخلاصة أن قدرة الطلاب على نطق الحروف الهجائية 76،00 بدرجة جيد جدا،ووجود العلاقة الإيجابية بين قدرة الطلاب على نطق الحروف الهجائية والتحصيل التعليمي لمادة الإملاء في المرحلة المتوسطة الصف الثاني بمعهد الكوثر.